Формування комунікативної компетентності студентів – майбутніх соціологів як можливості підвищення якості інтерв’ювання - Ідрісов, Бахтійор; Идрисов, Бахтиёр; Idrisov, Bakhtiior (My University, 2016)
Помилки в соціологічному прогнозуванні досить часто пов’язані з недостатньою комунікативною компетентністю інтерв’юерів. Тому протягом трьох років зі студентами МДПУ ім. Б. Хмельницького проводили дослідження, у результаті якого визначено дії педагога з формування в майбутніх соціологів комунікативного складника професійної діяльності та вироблено критерії її оцінювання. Як інструмент дослідження застосовано «соціолінгвічний метод визначення комунікативної компетентності», який дає змогу оптимізувати підготовку інтерв’юерів за конкретної теми дослідження. Результати роботи засвідчили, що комунікативною компетентністю соціолога є сформовані в процесі професійного навчання вміння, навички й можливості застосування особистісного потенціалу. Ошибки в социологическом прогнозировании достаточно часто связаны с недостаточной коммуникативной компетентностью интервьюеров. Поэтому на протяжении трех лет со студентами МДПУ им. Б. Хмельницкого проводили исследование, в результате которого определены действия педагога по формированию у будущих социологов коммуникативной составляющей профессиональной деятельности и выработаны критерии ее оценивания. В качестве инструмента использован «социолингвический метод определения коммуникативной компетентности», позволяющий оптимизировать подготовку интервьюеров по конкретной теме исследования. Результаты работы показали, что коммуникативная компетентность социолога представляет собой сформированные в процессе профессионального обучения умения, навыки и возможности применения личностного потенциала. Errors in the sociological forecasting often enough to overcome the problems associated with the unavailability of the respondents, and, accordingly, a lack of communicative competence of interviewers. So, for three years with students MDPU n. B. Khmelnytsky conducted a study in which identified actions of the teacher on formation at the future sociologists communicative component of professional practice and developed criteria for its evaluation. As a tool designed «Sociolinguistic method of determining the communicative competence» to optimize the training of interviewers on a specific topic of research. The study, conducted by the authors showed that the criteria for participation in the study must comply with the minimum level of «adequate, but need to further develop knowledge and skills in professional and everyday communication». The results of research show that the communicative competence of the future sociologists formed and developed in the course of vocational training and is acquired abilities, skills and potential of personal communicative potential in the working process and everyday communication. In the context of the requirements for the formation of future sociologists general professional competence of teachers of action should be aimed at the mastery of the communicative competence of the students, which reflects the level of Maturity of sociological thinking and relevant professional conceptual apparatus.
Formation the Communicative Competence of the Future Sociologist as the Possibility of Raising Quality of Interviewing
Keywords: загальнопрофесійна компетентність; інтерв’ювання; комунікативні компетенції; общепрофессиональная компетентность; интервьюирование; коммуникативные компетенции; professional competence; interviewing; communication competence